Corporate Social Responsibility And its Role in Achieving Sustainable Development in Egypt - Balbaa, Mohamed (The Arab Journal of Administration, 2018)
Sustainable development is based on employment creation, education, poverty alleviation and rational environmental management. While all governments, civil society organizations and the academic community should take part in this effort, companies have a critical role to play in contributing to the advancement of communities working in, and can play this role through CSR initiatives that are in line with national development goals. Achieving sustainable development in Egypt is the cornerstone for achieving long-term prosperity and long-term stability. As a viable national entity, companies should participate in sustainable development and contribute to the improvement of their societies and therefore need to align themselves with these national goals of sustainable development, using the powerful CSR tool to help achieve these goals. There is no doubt that there is a close relationship between corporate social responsibility and the concept of corporate governance as one of its most important pillars on the one hand and sustainable development on the other. Just as good corporate governance enhances the prospects for sustainable development in countries as a way to help leaders and managers achieve sustainable development. Following corporate governance principles will create the necessary precautions against corruption and mismanagement, while promoting transparency in economic life and combating institutional resistance to reform. The strength of economic sustainability and associated institutional reforms , Which will provide the necessary basis for improving the governance situation in the public and private sectors through the application of corporate social responsibility in light of the environment and social justice and create opportunities for future generations. In this research, we attempt to shed light on CSR and the importance of applying its mechanisms to companies in Egypt through awareness of the need to take into consideration ethical, social and environmental values ​​as well as commercial profitability in order to reach a sustainable institution and thus a sustainable economy.